Association of attention-deficit/hyperactivity disorder and atopic eczema modified by sleep disturbance in a large population-based sample. Issue 3 (19th August 2009) - Romanos, Marcel; Gerlach, Manfred; Warnke, Andreas; Schmitt, Jochen
Abstract : Background: A cross-sectional study was performed in a population-based German sample (n=13 318 children and adolescents aged 3–17) to replicate the recently reported independent association of atopic eczema (AE) and attention-deficit/hyperactivity disorder (ADHD) and to further investigate the role of environmental and behavioural factors. Methods: The odds ratio (OR) was calculated with allergic comorbidity and various environmental factors considered as confounders and sleeping problems hypothesised to act as a potential effect modifier. Results: The lifetime prevalence of AE and ADHD was 14.7% (male 14.4%; female 14.9%) and 4.9% (male 7.8%; female 2.0%), respectively. There was an association between ADHD and AE (OR 1.54; 95% CI 1.24 to 1.93; p<0.001), which was independent of sociodemographic factors, parental smoking, breastfeeding, number of siblings, perinatal health problems, and atopic comorbidity. Further analyses of a subgroup of 6484 children age 3–11 confirmed the hypothesis that the association between AE and ADHD was modified by sleeping problems (interaction effect AE*sleep problems OR 2.02 95% CI 1.03 to 3.97; p=0.04). There was a strong association between AE and ADHD in children with SP (OR 2.67 95% CI 1.51 to 4.71; p=0.001; n=1112), but not in children without SP (OR 1.24 95% CI 0.83 to 1.84; p=0.30; n=5796). Conclusions: ADHD and AE appear to be strongly and independently associated in children with sleeping problems, but not in children without sleeping problems. A substantial part of diagnoses met for ADHD might be engendered by the presence of AE and concomitant sleeping problems.